1999
DOI: 10.1086/306742
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Star Mass Measurements. I. Radio Pulsars

Abstract: There are now about fifty known radio pulsars in binary systems, including at least five in double neutron star binaries. In some cases, the stellar masses can be directly determined from measurements of relativistic orbital effects. In others, only an indirect or statistical estimate of the masses is possible. We review the general problem of mass measurement in radio pulsar binaries, and critically discuss all current estimates of the masses of radio pulsars and their companions. We find that significant con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
580
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 626 publications
(636 citation statements)
references
References 64 publications
53
580
3
Order By: Relevance
“…Unfortunately, no decisive argument has been given so far in favor of the stiff, moderate or soft equations of state. One can definitely rule out only the ultra-soft equations of state which give the maximum stellar mass lower than 1.44 M ⊙ , the accurately measured mass of the Hulse-Taylor pulsar (Thorsett and Chakrabarty 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no decisive argument has been given so far in favor of the stiff, moderate or soft equations of state. One can definitely rule out only the ultra-soft equations of state which give the maximum stellar mass lower than 1.44 M ⊙ , the accurately measured mass of the Hulse-Taylor pulsar (Thorsett and Chakrabarty 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, modern theoretically computed equations of state (EOS) generally predict somewhat larger moments of inertia for stars more massive than 1M , a group which includes all neutron stars with measured masses (see Ref. [43]). Therefore the dependence on the moment of inertia should be considered.…”
Section: B Dependence On the Moment Of Inertiamentioning
confidence: 99%
“…Mixing of hyperons only already leads to appreciable softening of the EOS [45,[49][50][51][52][53][54][55][56][57][58]. Hence, further development of kaon condensates in hyperonic matter would make the EOS too soft to obtain the observed neutron star masses ∼ 1.4M ⊙ [86,87] or even much larger masses∼ 2.0M ⊙ if the recent analyses from the observations of the quasi-periodic oscillations (QPO) [88] are confirmed [51]. Relativistic effects may help weaken the softness of the EOS, since it has been shown that the energy gain of kaon condensation coming from the s-wave scalar attraction is suppressed by relativistic effects [8,4]: As a kaon condensate develops, the effective nucleon mass M * decreases due to the scalar attraction, which leads to suppression of the scalar density,…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%